Primary fixation of AO type-C fracture of the distal radius with volar locking plates. A cross-sectional study of patient rated outcomes at Hospital Tengku Ampuan Afzan - Hassan, Mohd Sallehuddin; Zakaria@Mohamad, Zamzuri; Sharifudin, Mohd Ariff; Awang, Mohd Shukrimi; Mohamed Amin, Mohamed Azril; Mohd Yusof, Nazri (Faculty of Medicine, International Islamic University Malaysia, 2014)
Introduction: This is a cross-sectional study of 37 patients with AO type C (complete intra-articular) fractures of the distal radius, evaluating the functional, anatomical, and patient rated outcomes one year after primary fixation with a volar locking plate. Methods: Functional outcomes were assessed based on the grip strength, and the range of motion of forearm and wrist. Anatomical outcomes were assessed based on the radial inclination, radial height, volar tilt, and articular step or gap. Patient rated outcome was measured with a Disability of arm, shoulder and hand (DASH) questionnaire. Results: One year after surgery, 24 (64%) patients achieved good and excellent anatomical results, and DASH scores were acceptable in 73% of patients. Most of the patients had achieved 80% of their grip strength. The mean DASH score of 12.3 was comparable with other studies. Grip strength, radial inclination and volar tilt had a significant correlation with the DASH score. Conclusion: Volar locking plates can be used to achieve optimal reduction in all three parameters in the treatment of AO type C fractures of the distal radius. Versatile fracture fragment reduction and angular stability enable rehabilitation hence obtaining good functional outcomes.